Involvement of spinal muscarinic and serotonergic receptors in the anti-allodynic effect of electroacupuncture in rats with oxaliplatin-induced neuropathic pain - Lee, Ji Hwan; Go, Donghyun; Kim, Woojin; Lee, Giseog; Bae, Hyojeong; Quan, Fu Shi; Kim, Sun Kwang (The Korean journal of physiology & pharmacology, 2016)
This study was performed to investigate whether the spinal cholinergic and serotonergic analgesic systems mediate the relieving effect of electroacupuncture (EA) on oxaliplatin-induced neuropathic cold allodynia in rats. The cold allodynia induced by an oxaliplatin injection (6 mg/kg, i.p.) was evaluated by immersing the rat's tail into cold water (4℃) and measuring the withdrawal latency. EA stimulation (2 Hz, 0.3-ms pulse duration, 0.2~0.3 mA) at the acupoint ST36, GV3, or LI11 all showed a significant anti-allodynic effect, which was stronger at ST36. The analgesic effect of EA at ST36 was blocked by intraperitoneal injection of muscarinic acetylcholine receptor antagonist (atropine, 1 mg/kg), but not by nicotinic (mecamylamine, 2 mg/kg) receptor antagonist. Furthermore, intrathecal administration of M2 (methoctramine, 10 µg) and M3 (4-DAMP, 10 µg) receptor antagonist, but not M1 (pirenzepine, 10 µg) receptor antagonist, blocked the effect. Also, spinal administration of 5-HT3 (MDL-72222, 12 µg) receptor antagonist, but not 5-HT1A (NAN-190, 15 µg) or 5-HT2A (ketanserin, 30 µg) receptor antagonist, prevented the anti-allodynic effect of EA. These results suggest that EA may have a signifi cant analgesic action against oxaliplatin-induced neuropathic pain, which is mediated by spinal cholinergic (M2, M3) and serotonergic (5-HT3) receptors.